2021
DOI: 10.1186/s12940-021-00695-1
|View full text |Cite
|
Sign up to set email alerts
|

Metal biomarker mixtures and blood pressure in the United States: cross-sectional findings from the 1999-2006 National Health and Nutrition Examination Survey (NHANES)

Abstract: Background The objective of this study was to identify conditional relationships between multiple metal biomarkers that predict systolic and diastolic blood pressure in the non-institutionalized United States adult population below the age of 60. Methods We used inorganic exposure biomarker data and blood pressure data from three cycles (1999–2004) of the National Health and Nutrition Examination Survey (NHANES) to construct regression trees for bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…A recent report indicated that one-third of Chinese adults had MetS due to the rapid socio-economic growth within a short time [8]. Growing evidence suggested that essential elements might impact the onset and progression of MetS [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent report indicated that one-third of Chinese adults had MetS due to the rapid socio-economic growth within a short time [8]. Growing evidence suggested that essential elements might impact the onset and progression of MetS [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Possible reasons for these discrepancies include differences in population demographics, exposure patterns and levels, mixture components, study designs, biospecimens measured, the timing of exposure and outcome assessment, population-specific unmeasured confounding, CVD outcome definitions, and the statistical approaches used [69]. The majority of studies were either cross-sectional in design (n = 13) [39,[42][43][44][45][46][47][49][50][51][52][53][54] or prospective cohort studies (n = 10) [38,[55][56][57][58][59][60][61][62][63]. Cardiovascular outcomes and risk factors were categorized into four groups: (i) blood pressure (BP) and hypertension, (ii) preeclampsia, (iii) dyslipidemia and serum lipid markers, and (iv) clinical CVD outcomes, including stroke, coronary heart disease (CHD), and myocardial infarction (MI).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were conducted in the USA, followed by 9 in China ( Table 2 ). While 6 out of the 10 USA studies were based on NHANES data [ 42 , 43 , 44 , 45 , 46 , 47 ], none were excluded as they focused on unique combinations of metal components, evaluated different CVD-related outcomes, or used different mixtures analysis methods. Sample sizes ranged between 127 (a panel study of adults in China [ 48 ]) to 10,818 (a cross-sectional study conducted in the USA NHANES [ 43 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations